2021
DOI: 10.1111/1462-2920.15617
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal hydrologic and geologic forcing drive hot spring geochemistry and microbial biodiversity

Abstract: Hot springs integrate hydrologic and geologic processes that vary over short-and long-term time scales. However, the influence of temporal hydrologic and geologic change on hot spring biodiversity is unknown. Here, we coordinated near-weekly, cross-seasonal ($140 days) geochemical and microbial community analyses of three widely studied hot springs with local precipitation data in Yellowstone National Park. One spring ('HFS') exhibited statistically significant, coupled microbial and geochemical variation acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 62 publications
4
14
0
Order By: Relevance
“…S1A and B). The recovery of Desulfurococcales MAGs and 16S rRNA genes in GGS063 versus 16S rRNA gene amplicons from other hot springs is likely attributable to the primers (515F-806R [ 36 ]) that were used to amplify 16S rRNA genes in the previous study that are now known to be biased against the amplification of key groups of Archaea ( 37 ), including members of the Desulfurococcales ( 38 ). Collectively, these data indicate that the taxonomic and functional insights generated from MAGs from planktonic and sediment communities in GGS063 are reflective of other communities inhabiting circumneutral to alkaline springs in YNP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1A and B). The recovery of Desulfurococcales MAGs and 16S rRNA genes in GGS063 versus 16S rRNA gene amplicons from other hot springs is likely attributable to the primers (515F-806R [ 36 ]) that were used to amplify 16S rRNA genes in the previous study that are now known to be biased against the amplification of key groups of Archaea ( 37 ), including members of the Desulfurococcales ( 38 ). Collectively, these data indicate that the taxonomic and functional insights generated from MAGs from planktonic and sediment communities in GGS063 are reflective of other communities inhabiting circumneutral to alkaline springs in YNP.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the similarity of GGS063 communities to those of other circumneutral hot springs in YNP, 16S rRNA genes were retrieved from the IMG database for both the sediment and planktonic communities from GGS063 and compared against sediment and planktonic community compositions of 15 other hot springs previously reported in Colman et al ( 13 ). Briefly, the metagenome-derived 16S rRNA genes were subject to alignment to the Silva reference database with operational taxonomic units (OTU) representatives from the other 30 communities, trimmed to the length of the V4-V5 hypervariable region used in the previous study, clustered into OTUs at the 97% nucleotide sequence identity level, and classified against the Silva database, all as described previously ( 38 ). The GGS063 OTUs were added to those from the previous data set based on clustering with the previously identified representative 16S rRNA gene sequences.…”
Section: Methodsmentioning
confidence: 99%
“…These sites are both replenished via deeply-sourced hydrothermal fluids that exhibit limited interaction with groundwater ( Bignall et al, 2010 ; Gallagher et al, 2020 ). The rate of physicochemical change for these fluids would be much slower than other inputs to shallower (i.e., acidic) geothermal springs, such as meteoric and/or groundwater, which are more readily affected by the level of the water table and atmospheric events ( Campbell et al, 2017 ; Colman et al, 2021 ). Thus, the microbial communities of geothermal features with deeply sourced hydrothermal fluids are sustained by a more constant environmental niche, which consequently promotes a stable ecosystem structure.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen geothermal features in Croatia also demonstrated a lack of seasonality within resident microbial community structures (Mitrović et al, 2022). However, other studies have shown a seasonality effect in microbial mats, water and sediment samples from geothermal features, where seasons coincided with dichotomous weather patterns (e.g., monsoon rainfall or snowmelt; Lacap et al, 2007;Briggs et al, 2014;Colman et al, 2021). Time-dependent differences to alpha diversity (i.e., richness and relative abundances), but not community dissimilarity have been reported in two separate studies (Lacap et al, 2007;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have examined the microbial dynamics in hot spring systems that encompass a wide range of potential variables, their impact on different microbial communities, and have resulted in variable conclusions regarding how dynamic these systems are. Work that examined seasonal impacts on planktonic microbial hot spring communities linked precipitation as a major driver of community structure (Briggs et al, 2014), while an additional study found that precipitation impacts were variable between springs and potentially dependent on aquifer recharge (Colman et al, 2021). Other work found temperature as the greatest selector for microbial communities in sediments and planktonic communities (Guo et al, 2020; Wang et al, 2013), and that planktonic communities were stable temporally while sediment communities were more diverse and dynamic during the sampling period (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%